Validation of two‐channel sequencing‐by‐synthesis for noninvasive prenatal testing of fetal whole and partial chromosome aberrations. (15th February 2016) - Neveling, Kornelia; Tjwan Thung, Djie; Beulen, Lean; van Rens‐Buijsman, Wendy; Gomes, Ingrid; van den Heuvel, Simone; Mieloo, Hanneke; Derks‐Prinsen, Irma; Kater‐Baats, Ellen; Faas, Brigitte H. W.
Abstract: Objective: To validate Illumina's two‐channel NextSeq 500 sequencing system for noninvasive prenatal testing (NIPT) of fetal whole chromosome and partial aberrations. Methods: A total of 162 plasma samples, previously sequenced for NIPT on a SOLiD 5500xl platform, were sequenced on the NextSeq 500 using 75‐bp single‐end sequencing, followed by analysis using the WISECONDOR algorithm. Results: For whole chromosome aneuploidy detection, all samples were classified correctly (in total 3× T13, 3× T18, 8× T21 and 145× euploid). Three partial aberrations (36‐Mb terminal loss of 5p, 14‐Mb gain on 18p and 33‐Mb terminal loss of 13q) were also correctly identified. Fetal fractions in 34 male samples sequenced on both the SOLiD 5500xl and NextSeq 500 platform showed no significant difference. To test robustness, two sample sets, containing both euploid and aneuploid samples, were sequenced on different NextSeq 500 machines, revealing identical results. With unchanged laboratory flow, the NIPT turnaround time could be reduced from 15–16 calendar days to 7–8 calendar days, after switching from the SOLiD 5500xl to the NextSeq 500 platform. Conclusions: The NextSeq 500 platform can be used for NIPT to detect both whole and partial chromosome aberrations. It has fast turnaround times and is suitable for mid‐sized laboratories. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Noninvasive prenatal testing has been introduced in the clinical setting, based on excellent results obtained in validation studies carried out on different next‐generation sequencing platforms. What does this study adds? This is the first study demonstrating the rapid and robust performance of noninvasive prenatal testing using the two channel‐technology NextSeq 500 sequencing platform, a platform which is very suitable for mid‐sized laboratories.